2012
DOI: 10.1172/jci64413
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus autoantibodies generated through somatic mutations target the desmoglein-3 cis-interface

Abstract: Pemphigus vulgaris (PV) is an autoimmune blistering disease of skin and mucous membranes caused by autoantibodies to the desmoglein (DSG) family proteins DSG3 and DSG1, leading to loss of keratinocyte cell adhesion. To learn more about pathogenic PV autoantibodies, we isolated 15 IgG antibodies specific for DSG3 from 2 PV patients. Three antibodies disrupted keratinocyte monolayers in vitro, and 2 were pathogenic in a passive transfer model in neonatal mice. The epitopes recognized by the pathogenic antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 45 publications
8
160
2
1
Order By: Relevance
“…There is growing evidence, however, that IgG4 antibodies can be pathogenic: IgG4 antibodies against desmoglein cause a skin-blistering disease, termed pemphigus (50), and IgG4 antibodies to the phospholipase A2 receptor are thought to contribute to membranous nephropathy (51). Moreover, IgG4 autoantibodies to Leucine-rich glioma inactivated 1 (Lgi1), a regulator of the voltage-gated potassium channel, are thought to be responsible for limbic encephalitis (52).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence, however, that IgG4 antibodies can be pathogenic: IgG4 antibodies against desmoglein cause a skin-blistering disease, termed pemphigus (50), and IgG4 antibodies to the phospholipase A2 receptor are thought to contribute to membranous nephropathy (51). Moreover, IgG4 autoantibodies to Leucine-rich glioma inactivated 1 (Lgi1), a regulator of the voltage-gated potassium channel, are thought to be responsible for limbic encephalitis (52).…”
Section: Discussionmentioning
confidence: 99%
“…A paper that was published recently characterized pathogenic mAbs that cause pemphigus vulgaris (40). They reverted the somatic mutations from four mAbs against desmoglein-3 (DSG3) and found that the unmutated antibodies did not bind to DSG3.…”
Section: Discussionmentioning
confidence: 99%
“…Direct steric inhibition apparently mimics the so-called tryptophan-swap between interacting Dsg3 molecules which hampers cis-and trans-interaction (Di Zenzo et al, 2012;Spindler et al, 2013;Yamagami et al, 2010). As inhibition of Dsg3 binding contributes to loss of cell cohesion in vivo and in vitro (Heupel et al, 2009b(Heupel et al, , 2008Spindler et al, 2013), it is possible that this mechanism alone is suffi cient to cause blister formation in some cases, especially when blistering is mechanically induced (Mao et al, 2013;Saito et al, 2012).…”
Section: Role Of Signaling Induced By Autoantibodies In Pemphigus Patmentioning
confidence: 99%